State-owned enterprises, fiscal transparency, and the circumvention of fiscal rules: the case of Germany - Heinemann, Friedrich; Nover, Justus; Steger, Paul (European journal of political economy, 2025)
State-owned enterprises (SOEs) provide opportunities for a more flexible and market-based provision of public services. At the same time, they may impair fiscal transparency and offer politicians discretion in the presence of strict fiscal rules if these only constrain the core budget. Using a comprehensive micro-data set of German SOEs, this paper studies a possible impact of the German debt brake on SOEs by tracking changes in financial indicators at the firm level that would hint to a circumvention of the rule. The identification exploits that the mounting compliance pressures over the lagged implementation of the debt brake from 2010 to 2020 differs across the 16 states. The results show that SOEs in fiscally more constrained states exhibit a stronger decrease in equity and reserves and a higher increase in debt compared to SOEs in less constrained states and the shorter the distance to the 2020 deadline. This result is based on a combined sample of state and municipal SOEs, a finding pointing towards the vertical spillover of a fiscal rule.
Online veröffentlicht: 19. Dezember 2024, Artikelversion: 19. Dezember 2024
Gesehen am 27.05.2025
Keywords: Aufsatz in Zeitschrift